Routine management of postoperative delirium outside the ICU: Results of an international survey among anaesthesiologists. Issue 4 (19th January 2020) - Bilotta, Federico; Weiss, Bjoern; Neuner, Bruno; Kramer, Sylvia; Aldecoa, César; Bettelli, Gabriella; Sanders, Robert D.; Delp, Simon M.; Spies, Claudia D.
Abstract : Background: Postoperative delirium (POD) is a severe brain dysfunction. Although data indicate a high relevance, no survey has investigated the routine practice to monitor delirium outside the ICU setting after surgery. Prior to publishing of the new European Society of Anaesthesiology (ESA) guidelines on POD, an international survey was conducted to assess current practice. Methods: European Society of Anaesthesiology‐endorsed online survey; Trial Registration : NCT‐identifier: 02513537. Results: In total, 566 respondents from 62 countries accessed, and 564 (99.6%) completed the survey (completion rate). Overall, 385 (68%) of the respondents reported that delirium is either "very relevant" or "relevant" for their daily clinical practice. In all, 38 (7%) of the respondents routinely monitor for delirium in >50% of all patients. Asked on the monitoring time point, more than half (n = 308, 55%) indicated to screen before or at recovery room discharge, 235 (42%) up to the first postoperative day, 143 (25%) up to 3 days, and 77 (14%) up to 5 postoperative days. Although there is a lack of long‐term monitoring, nearly all respondents (n = 530, 94%) reported to treat delirium. Availability of EEG/EMG‐based monitoring to assess the depth of anaesthesia was high in the study group (n = 547, 97%) and was used by more than one‐third of the respondents to reduce risk of burst suppression (n = 189, 34%). Conclusion: Although delirium is perceived as a relevant condition among anaesthesiologists, there is a high demand for implementing monitoring strategies after publishing of the POD Guideline. The survey shows that tools necessary for POD Guideline implementation are available in the centres represented by the respondents.